Effectiveness test on hardness performance of plastic waste and sawdust composite - Saiful Bahri, Mohamed; Martini, Muhamad@Mohd Saufi; Wawan Trisnadi, Putra (2019)
The strength of a material is one option used to determine the use of forms. The use of plastics on product packaging is an efficient choice because plastics is light, practical and easy to forms. This study is done to measure the plastic waste hardness of mixed HDPE and PET type with teak tree sawdust which melted into two portions by the amount of 18 gram. This study finds the highest hardness index was achieved by the mixture of 1.5 gram of sawdust, 5 gram PET and 11.5 gram HDPE with the hardnesss point of 131. 3 N/mm under the 5000 gram pressure and temperature of 100°C while the lowest point of 86.6 N/mm by the mixture of 1 gram sawdust, 625 gram PET and 10.7 gram HDPE under the 5000 gram pressure and temperature of 100°C. It can be seen that the lower the temperature of the mixture compositions, the better the hardness because the mixture is merged and binded better.